A Compact Grating-Type Labyrinthine Acoustic Metasurface for Broadband Multifunctional Wavefront Control - Zelong Wang; Yiming Gu; Yong Cheng; Huichuan Zhao (Crystals, 2025)
This study presents the design and numerical validation of a grating-type labyrinthine acoustic metasurface capable of full 0–2π phase modulation with high transmission efficiency. By tuning the tooth length of the subwavelength unit cells, precise control of the transmission phase is achieved while maintaining a high transmission coefficient across the operational bandwidth. The proposed metasurface structure is evaluated through comprehensive finite element simulations using COMSOL Multiphysics 6.0 at a center frequency of 4000 Hz. The following five core wavefront manipulation functionalities are demonstrated: complete phase modulation, anomalous refraction, planar wave focusing, cylindrical-to-plane wave conversion, and cylindrical wave focusing. Each functionality is validated across a 400 Hz frequency range to confirm robust broadband performance. The metasurface exhibits minimal phase degradation and maintains high spatial coherence across varying frequencies, highlighting its potential for applications in acoustic beam steering, imaging, and wavefront engineering.